THE INFLUENCE OF BAIT TO WARD CATH RESULT RAWAI IN THE RIVER WATER KAMPAR KIRI MUARA SAKO KELURAHAN LANGGAM KECAMATAN LANGGAMKABUPATEN PELALAWAN - Teti Ambarani; Pareng Rengi; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this study is to determine the best bait of three types of natural bait on longline catches in Sub Langgam District of LanggamPelalawan. This study was conducted in November 2016, in the waters of the river Kampar Kiri District of Muara Sako Village Idioms Langgam Pelalawan. The study was conducted using longline gear with different lures treatment is to feed crickets (Gryllidae), Sepat pearls (Trichogaster leeri), weaver ant eggs (Oecophylla). The method used in this research is the experimental method. The number of replications of 10 repetitions. The data were processed using a statistical test with SPSS 20.0 software on a test level of95% with normality test and one way ANOVA test. The results showed that different types of lures that affect the catch, type of fish caught by longline gear overall during the study based on the percentage amount (kg), namely: slice, juaro, Tapah, baung usual, baung mice, catfish. Fish juaro is a type of fish that most captured during the research that is equal to 17 tails of the overall catch.Keywords: Bait, line fishing, Kampar river left